The commercialisation of the celebrity brand and the exploitation thereof - Bester, Lukas Marthinus (Department of Commercial Law, 2016)
Celebrities' prominence in our daily lives cannot be underestimated. It is therefore quite hard to imagine that little has been written about the confluence of celebrity and the law. Celebrity law, particularly the mercantile element thereof, deserves greater attention. Celebrity's freely use their image to make money - these actions must be governed by an established body of law. The law must assist the celebrity in his commercial activities and must offer safety nets for when others unfairly exploit his celebrity brand. The topic will be divided into five points of discussion. First, the commercialisation of the celebrity brand will be discussed. Secondly, we will take a closer look at image rights. Thirdly, the delictual claim of passing off as it pertains to celebrities will be discussed. Fourthly, trade marked celebrities will be considered. And finally our focus will be drawn to the personality right of reputation and how it can be influential for the capitalist celebrity's sake. It is imperative to fully understand the celebrity phenomenon. Through the ages humankind has naturally sought out leaders in an array of fields. We need to grapple with the oddity of this phenomenon to understand the position of these modern societal leaders. The commercialisation of the celebrity brand will be explored. As societal leaders, celebrities are in the remarkable position to utilise their renown for their own benefit. Attention economy is a concept relating to the celebrity's ability to exploit his fame for commercial gain. This theory deals with the association of capital gain with broad-based, far-reaching image recognition. The niceties of attention economy will be explored to offer us insight into the ability of a celebrity to use his fame to make a profit. Attention economy is a theory aligning itself with image rights. Image rights are the commercial sales aspect of the celebrity entity, offering it legal security and a reactionary arsenal.